AKT2, a putative oncogene encoding a member of a subfamily of protein-serine/threonine kinases, is amplified in human ovarian carcinomas. - Cheng, J Q (1992)
We isolated cDNA clones containing the entire coding region of the putative oncogene AKT2. Sequence analysis and in vitro translation demonstrated that AKT2 encodes a 56-kDa protein with homology to serine/threonine kinases; moreover, this protein contains a Src homology 2-like domain. AKT2 was shown to be amplified and overexpressed in 2 of 8 ovarian carcinoma cell lines and 2 of 15 primary ovarian tumors. AKT2 was mapped to chromosome region 19q13.1-q13.2 by fluorescence in situ hybridization. In the two ovarian carcinoma cell lines exhibiting amplification of AKT2, the amplified sequences were localized within homogeneously staining regions. We conclude that AKT2 belongs to a distinct subfamily of protein-serine/threonine kinases containing Src homology 2-like domains and that alterations of AKT2 may contribute to the pathogenesis of ovarian carcinomas.